Emigration – culture – freedom. Vinko Nikolić and his dream about the independence - Przeklasa, Szymon (Balcanica Posnaniensia. Acta et studia, 2020)
We have the same enemy and the same motherland – the sentence by Vinko Nikolić is the essential one to describe his life, creativeness and a tragedy of the entity. This poet and emigre activist is well-known person in Republic of Croatia due to the loyalty to native culture and literature but also because being a controversial figure linked with the ultranationalist organization of Croatian Revolutionary Movement – Ustaša (which used to rule in Independent State of Croatia during World War II). The aim of the article is to show how Nikolić had become one of the most important Croat abroad during the existence of Socialist Federal Republic of Yugoslavia, how his connotations with Nazis really looked and how he changed views on the independence during being out of Croatia for almost 50 years.